Far-Field Testing Method of Spurious Emission Produced by HF RFID - Nikola Gvozdenovic; Ralph Prestros; Christoph F. Mecklenbräuker (International Journal of Antennas and Propagation)
We present measurements of spurious emission produced by high-frequency radio frequency identification (HF RFID) using carrier frequency of 13.56 MHz. HF RFID tags produce unwanted emission due to rectification and more generally due to nonlinearity of analog front end. Depending on the conducting material of an HF RFID coil and surrounding dielectric material, the coil behaves as more or less good antenna on some harmonic frequencies. Exact characterization and analysis of unwanted emission is important from the security perspective as well as from the perspective of interference with other systems. Consequently we measured the harmonics produced in the integrated circuitry and characterized radiation properties of the antenna. Finally we present the measurements of the spurious emission performed in a Gigahertz Transverse Electromagnetic (GTEM) cell.